Invitations and excuses that are not invitations and excuses: Gossip in Luke 14:18–20 - Eck, Ernest van (HTS teologiese studies, 2012)
In modern Western culture, gossip is seen as a malicious activity that should be avoided. In ancient oral-cultures, gossip as a cultural form did not have this negative connotation. Gossip was a necessary social game that enabled the flow of information. This information was used in the gossip network of communities to clarify, maintain and enforce group values, facilitate group formation and boundary maintenance and assess the morality of individuals. Gossip was a natural and spontaneous recurring form of social organisation. This understanding of gossip is used to interpret the two invitations and three excuses in the parable of the Feast (Lk 14:16a–23). The conclusion reached is that gossip, when understood as a social game, can be a useful tool to curb anachronistic and ethnocentristic readings of texts produced by cultures different from that of modern interpreters analysing these texts.